State Activities Impacts on the Residential Mobility Dynamics in Kandy and Suburbs - Balakrishnan, Arularasi; Hanjagi, Ashok D.; Narayanan, Priya (European Publisher, 2019)
Residential mobility is becoming a significant phenomenon in the contemporary urbanized world. City residents engage in mobility, which influences the shaping and reshaping of urban spaces. Residential mobility takes place due to several determinants, and urban development activities of the state are one of the significant structural factors among them. Kandy is the second-largest city in Sri Lanka which has been declared as a World Heritage City in 1988 by the UN. The Government of Sri Lanka has implemented urban policies, regional and city plans, urban development programmes, and strategic projects to preserve the unique urban characteristics of Kandy city. The objective is to assess how far state activities are responsible for the present residential mobility dynamics in Kandy city and its suburbs. The attributes of urbanisation and resultant neighbourhood changes discovered from the study conducted between 2016 - 2018, by collecting secondary data from relevant sources. Primary data which was acquired through indepth interviews, key informant interviews, unstructured discussions and observations comprises a part of the study. The study resulted in identifying the dynamics of an urban neighbourhood and its residential mobility changes. State activities are directly and indirectly stimulating the urban residential mobility diffusion waves towards Kundasale suburb that promote Kundasale as a popular residential suburb of Kandy city. The process, prospects, and products of urbanisation and residential mobility are discussed in detail in this paper.